Hydropeaking Operations of Two Run-of-River Mega-Dams Alter Downstream Hydrology of the Largest Amazon Tributary - Almeida, Rafael M.; Hamilton, Stephen K.; Rosi, Emma J.; Barros, Nathan; Doria, Carolina R. C.; Flecker, Alexander S.; Fleischmann, Ayan S.; Reisinger, Alexander J.; Roland, Fábio (Frontiers in Environmental Science, 2020)
Large storage dams have widely documented impacts on downstream aquatic environments, but hydroelectric dams with little or no capacity for storage of water inflows (i.e., run-of-river) have received less attention. Two of the world’s largest run-of-river hydropower dams (Jirau and Santo Antônio, Brazil) are located on the Madeira River, the largest tributary to the Amazon River. Here we examine whether the Madeira dams have affected downstream seasonal flood pulses and short-term (daily and sub-daily) flow dynamics. We show that the combined effects of these dams on seasonal flood pulses were modest. However, dam operations significantly increased day-to-day and sub-daily flow variability. The increase in short-term flow variability is largely explained by rapid, short-term variations in river flow caused by fluctuations in energy demand (hydropeaking). Both the magnitude of hydropeaking and the mean absolute day-to-day change in discharge downstream of the dams doubled after dam closure. In addition, the median hourly rate of water level change downstream of the dams was three times higher than upstream. Our findings highlight that even run-of-river dams on very large rivers such as the Madeira—whose average discharge at the dam site is larger than that of the Mississippi River at its mouth—can alter downstream hydrology through hydropeaking. Although little studied in tropical floodplain rivers, hydropeaking by large run-of-river dams may be detrimental to downstream aquatic organisms and human populations that utilize the river for navigation and fisheries.